Context-Tailored or User-Tailored: Which Approach Is Better for Violent Extremism Prevention Programs? - Lobato, Roberto Muelas (Crime & delinquency, 2025)
It is taken-for-granted that the one-size-fits-all approach does not work for extremism prevention programs. However, to what extent it is necessary to adapt these programs to the context or the user remains an unanswered question. This study attempts to provide evidence on which type of customization has a greater impact. Using data from the evaluation of the Fénix Andalucía prevention program, we analyzed if a reduction in the significance quest will reduce violent narratives by ameliorating deviant networks using multilevel structural equation modeling. The results showed that the average impact in the educational centers was not significant, while the individual experience of the participants was. It is concluded that prevention programs would benefit from user-tailored programs that enhance individual experiences.